Synergetic effect of training architects: combination of monotype and computer graphics (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article draws special attention to the need to renew the methodology of graphic training of architects, since the main indicators of their professional level and productive activity are the ability to use computer programs at a sufficiently creative level, which is an important addition to the formation of architects-artists. The research shows that there is insufficient attention to the monotype technique as a means of stimulating creativity and an incentive to search for visual and compositional solutions, as an influential factor in improving creative skills based on the principle of creative combination of monotype and computer graphics. The purpose of this article is to consider modern methods of graphic preparation and identify approaches to combining traditional printed graphics and computer graphics in the process of artistic and creative education. To substantiate the position that monotype in a new quality of application - a combination of monotype and computer graphics is of great importance for the formation of a future professional on the basis of the formation of a "synergistic" effect in the process of training architects.The study stipulates that the socio-cultural content of the "visual and project space" of architecture, which must simultaneously be "adapted" to the modern world together with modern forms and methods of training architects, requires updating the content-methodical component of education, which can no longer be based only on " traditional-system" approach to teaching graphics, and therefore a "combination of classical art education, creative and virtual. On the basis of the conceptual position of the study, in the aspect of attention to printed prints — Monotypes and the idea of the process of combining monotype and computer graphics as a synergistic, visual and creative basis of the combination of monotype and computer graphics - as a synthesis in monotype and computer graphics, the main methods, principles and results are revealed. On the basis of an example of a practical lesson on the topic of the relationship and influence of the constructive features of "graphics" on architecture as a monumental art and on the methods of teaching architects, the necessity of using Art-technology for creative education as a synthesis-combination of monotype and virtual computer graphics is determined for the manifestation of figurative and symbolic graphic "language and speech" of architecture. The conclusions establish the importance of studying the basics of monotype as an independent phenomenon of modern artistic creativity, and as an influential factor in improving students' creative skills, revealing their creative potential, monotype is a means of stimulating creativity in modern graphic design and the search for compositional solutions. It is argued that the combination of monotype and computer graphics creates a synergistic effect, helps to create original images on a limited plane. The application of this art technology for creative education determines the result of a synergistic effect, which is manifested in the presence of obtaining elements of novelty and the practical significance of the results. Prospects for further research. The researched problem-creative synthesis-combination of monotype and computer graphics requires the further invention of a special conceptual method of modern graphic training and the introduction of a "synergistic model" of education based on the idea of a holistic "integrative character of the informatization of modern education", which combines various artistic technologies in the process of formation artistic and creative personality.
Keywords: architecture; monotype; aquatype; florotype; graphic design; computer-digital programs; synthesis of arts; composition